Mazdutide, a dual agonist targeting GLP-1R and GCGR, mitigates diabetes-associated cognitive dysfunction: mechanistic insights from multi-omics analysisResearch in context - Wanqing Dong; Jie Bai; Qibin Yuan; Yingyu Zhang; Yongjiang Zhang; Ziyue Zhang; Maoxing Yang; Hanxiao Li; Ziyue Zhao; Hongwei Jiang (EBioMedicine)
Summary: Background: Cognitive impairment and dementia are highly associated with obesity and type 2 diabetes mellitus (T2DM). Recent studies have demonstrated that GLP-1 receptor agonists can improve cognitive function through brain activation in patients with T2DM, compared to other oral glucose-lowering drugs. Mazdutide, a dual agonist of the glucagon-like peptide-1 receptor (GLP-1R) and the glucagon receptor (GCGR), has been shown to simultaneously reduce body weight, blood glucose levels, and other comorbidities associated with obesity in patients with T2DM. While its insulinotropic and glucose-lowering effects through the GLP-1 pathway are well-established, mazdutide may also enhance energy expenditure via activation of the GCGR pathway. However, its potential impact on cognitive function remains to be elucidated. Methods: This study aimed to investigate the effects of mazdutide on cognitive behaviour and cerebral pathology in male db/db mice, a model of T2DM, in comparison to dulaglutide, a GLP-1 receptor agonist. All animal findings are applicable to male mice only. Behavioural tests were conducted to evaluate cognitive function, and pathological analyses were performed to assess neurodegenerative markers in the brain. Furthermore, transcriptomic, proteomic, and metabolomics analyses were employed to explore the underlying molecular mechanisms of mazdutide's effects. Findings: Compared to dulaglutide, mazdutide significantly improved cognitive performance in db/db mice, as evidenced by comprehensive behavioural tests. Pathological assessments revealed improvements in neuronal structure and brain tissue integrity in the mazdutide-treated group. Multi-omics analyses further identified distinct molecular pathways involved in neuroprotection, energy metabolism, and synaptic plasticity, suggesting that dual GLP-1/GCGR activation contributes to enhanced cognitive resilience. Interpretation: Our findings indicate that mazdutide, via its dual GLP-1/GCGR activation effects, exerts multifactorial improvements in cognitive function in the context of obesity and T2DM. These results suggest that mazdutide is a promising therapeutic option for mitigating cognitive deficits associated with metabolic disorders. Funding: Medical Science and Technology Research and Development Plan Major Project Jointly Constructed by the Henan Province and Ministerial Departments in China (No. SBGJ202301010).